ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PERUMAHAN BERSUBSIDI DI KAWASAN GRIYA HARAPAN BARU TAHAP 1 TANJUNG ANOM KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG - Sihombing, Betty Maria; Tobing, Artha L.; Sinaga, Kepler (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the factors that influence buyers' decisions in choosing subsidized housing in the Griya Harapan Baru Phase 1 area, Tanjung Anom, Pancur Batu District, Deli Serdang Regency. With the increasing need for decent housing in Indonesia, this study highlights the importance of aspects of price, location, building condition, and environment as variables that influence purchasing decisions. The method used is quantitative descriptive analysis with 65 respondents taken through a questionnaire. Data calculations using the SPSS version 25 data processing application with the results showing that there is an influence of price, location, building condition, and environment on the decision to purchase a type 36 house in the Griya Harapan Baru Phase 1 Tanjung Anom area with a determination level of 42.23% and 57.77% influenced by other factors not examined in this study.